Tampilan Nama Hari Berbasis Mikrokontroler Arduino Uno Menggunakan Saklar Tekan pada Project Board - Rozlinda Dewi; Dimas Agung Rozandi (Universitas Batanghari Jambi, 2019)
Arduino Uno is a variant of Arduino microcontroller board products. Arduino Uno uses AVR Atmega 328 microcontroller. With various advantages, In appearance (Display) the name of the day using Arduino Uno microcontroller technology is usually directly programmed. But sometimes the design of tools is moved when uploading the Arduino integrated development environment (IDE) program, therefore a push button (push button) is used to change the appearance of the day's name. For this study using a push switch (Push Button) in overcoming the error.